Clusters of Practice in Peritoneal Dialysis in France: Data from the Catheter Section of the RDPLF. Issue 2 (March 2018) - Lanot, Antoine; Bechade, Clémence; Verger, Christian; Fabre, Emmanuel; Vernier, Isabelle; Lobbedez, Thierry
Background: Peritonitis is a major cause of peritoneal dialysis (PD) failure. Recommendations for the prevention of peritonitis are available, but wide variations exist in the peritonitis rate among countries and PD units. The objective of this study was to describe the different pattern of practices in France. Methods: This was a retrospective, multicenter study based on data from the French Language Peritoneal Dialysis Registry. Center practices were described and mapped. Clusters of practices were sought in a hierarchical analysis and centers belonging to the same clusters of practices were mapped. Results: Data from 2, 770 catheters placed in 64 centers in France between 1 February 2012 and 31 December 2016 were considered. A median of 34 (ranging from 5 to 133) catheters was reported in each center. Twenty-eight (43.8%) centers routinely administered a prophylactic antibiotic prior to catheter placement, and 8 (12.5%) centers applied a local prophylactic antibiotic at the exit site, as recommended by International guidelines. The presence of a PD nurse specialized in PD or PD referent nephrologist was not associated with better adherence to guidelines. Practices were heterogeneous across centers. We identified 5 clusters of centers according to practice. Geographical proximity was not associated with homogeneity in practices. Conclusion: Peritoneal dialysis practices are heterogeneous in France, even those that are subject to International guidelines. Studies to identify associations between center-specific practices and PD patient outcomes remain mandatory. Efforts should be made to standardize the PD standards of care in France.